Manufacturing Difference: Police Responses to “Domestic Violence” - Khazaei Faten (Swiss Journal of Sociology, 2022)
Although previous research has criticized the racialization of violence against women, the tendency to link so-called “domestic violence” to migrant population remains popular in Switzerland. This article based on an ethnographic study of a police emergency unit, argues against the thesis according to which domestic violence is more frequent (or more serious) in migrant populations. It examines the “Sri Lankan case”, a prevailing narrative in this institution, to show how the police officers manufacture difference between similar cases.